A cellulose-modified alumina / epoxy resin material and its preparation method and application
By introducing cellulose-modified alumina particles into the epoxy resin and increasing their binding force through specific chemical modification methods, forming cellulose-modified alumina/epoxy resin materials with high mechanical strength, toughness and thermal stability, the limitations of traditional epoxy resin materials in terms of toughness and impact resistance are solved, suitable for high-temperature industrial applications and reduce environmental impact.
Patent Information
- Application Number
- CN202411091085.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-09
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-08-09
AI Technical Summary
Traditional epoxy resin materials have limitations in toughness and impact resistance, making it difficult to meet the needs of high-performance applications.
By introducing cellulose-modified alumina particles into the epoxy resin, the chemical activity of the alumina particles is improved by using a specific chemical modification method to combine with microcrystalline cellulose more effectively, thereby forming a cellulose-modified alumina/epoxy resin material with high mechanical strength, toughness and thermal stability.
It significantly improves the mechanical strength, toughness and thermal stability of the material, enhances the load tolerance and impact resistance of the material, is suitable for high-temperature industrial applications, while reducing the impact on the environment and improving the environmental friendliness of the material.
Smart Images

Figure BDA0004986595770000191 
Figure BDA0004986595770000201
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of epoxy resin materials, and in particular relates to a cellulose modified alumina / epoxy resin material and a preparation method and application thereof. Background Art
[0002] Epoxy resins are widely used in many fields such as aerospace, electronic packaging, coatings and construction due to their excellent mechanical properties, bonding properties and chemical stability. They are thermosetting plastics that can provide high strength, excellent chemical resistance and heat resistance after hardening. However, despite the many advantages of epoxy resins themselves, they still have limitations in certain high-performance applications, especially in terms of toughness and impact resistance.
[0003] Traditional epoxy resins are usually improved by adding fillers, such as inorganic fillers (alumina, silicate, etc.) or organic fillers (carbon fiber, glass fiber, etc.). These fillers can improve the mechanical strength and thermal stability of epoxy resins to a certain extent, but the traditional epoxy resin modification methods are still not effective in improving the mechanical strength and toughness of the material.
[0004] In summary, it is very necessary to provide a cellulose modified alumina / epoxy resin material and a preparation method and application thereof. Summary of the invention
[0005] In order to solve one or more technical problems existing in the prior art, the present invention provides a cellulose modified alumina / epoxy resin material and a preparation method and application thereof. The present invention combines cellulose modified alumina particles with epoxy resin to obtain a cellulose modified alumina / epoxy resin material that can significantly improve the mechanical strength, toughness and thermal stability of the material, and the material is suitable for industrial applications requiring high performance and high temperature resistance.
[0006] In a first aspect, the present invention provides a method for preparing a cellulose-modified alumina / epoxy resin material, the method comprising the following steps:
[0007] (1) uniformly dispersing aluminum oxide particles with toluene to obtain an aluminum oxide dispersion;
[0008] (2) adding 3-(2,3-epoxypropoxy)propyltrimethoxysilane to the alumina dispersion and stirring for reaction, and then centrifuging, washing and drying to obtain modified alumina particles;
[0009] (3) adding modified alumina particles, microcrystalline cellulose, potassium carbonate and ethanol aqueous solution into toluene and stirring to react, and then centrifuging, washing and drying to obtain cellulose modified alumina particles;
[0010] (4) Add cellulose-modified alumina particles to bisphenol A epoxy resin and mix them evenly to obtain a cellulose-modified alumina / epoxy resin material.
[0011] Preferably, in step (1), the dosage ratio of the alumina particles to the toluene is 1 g: (40-60) mL; in step (2), the dosage ratio of the alumina particles contained in the alumina dispersion to the 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1 g: (1-3) mL; in step (3), the dosage ratio of the modified alumina particles to the toluene is 1 g: (40-60) mL, the mass ratio of the modified alumina particles to the microcrystalline cellulose is 1: (0.5-1.5), and the dosage ratio of the modified alumina particles to the ethanol aqueous solution is 1 g: (2-4) mL; in step (3), the ethanol aqueous solution is formed by mixing ethanol and water in a volume ratio of (7-9): 1; and / or in step (3), the mass dosage of potassium carbonate is 1.5-2.5% of the mass dosage of the microcrystalline cellulose.
[0012] Preferably, in step (2) and / or step (3), the stirring reaction temperature is 80 to 100° C., and the stirring reaction time is 18 to 36 hours.
[0013] Preferably, the mass amount of the cellulose modified alumina particles is 1 to 5% of the mass amount of the bisphenol A epoxy resin; and / or the cellulose modified alumina particles are added to the bisphenol A epoxy resin in the form of a dispersion, and step (4) is: using tetrahydrofuran to ultrasonically disperse the cellulose modified alumina particles uniformly to obtain a cellulose modified alumina tetrahydrofuran dispersion, and then adding the cellulose modified alumina tetrahydrofuran dispersion to the bisphenol A epoxy resin and stirring uniformly to obtain a mixture, and then vacuum degassing the mixture and removing the tetrahydrofuran by rotary evaporation to obtain a cellulose modified alumina / epoxy resin material, and the mass ratio of the cellulose modified alumina particles to the tetrahydrofuran is 1: (10 to 15).
[0014] Preferably, the particle size of the aluminum oxide particles is 20 to 60 nm; the particle size of the microcrystalline cellulose is 3 to 60 μm; and / or the bisphenol A type epoxy resin is E51 liquid epoxy resin.
[0015] In a second aspect, the present invention provides a cellulose-modified alumina / epoxy resin material prepared by the preparation method described in the first aspect of the present invention.
[0016] In the third aspect, the present invention provides the use of a cellulose-modified alumina / epoxy resin material prepared by the preparation method described in the first aspect of the present invention in the preparation of epoxy resin mold materials or epoxy resin molds, wherein the epoxy resin mold material comprises a cellulose-modified alumina / epoxy resin material, a bisphenol F epoxy resin, a polyamide curing agent, an accelerator and an aqueous phase filler.
[0017] Preferably, the mass ratio of the cellulose modified alumina / epoxy resin material, the bisphenol F epoxy resin, the polyamide curing agent, the accelerator and the aqueous phase filler is 10:(2-8):(3-8):(0.5-2):(50-80).
[0018] Preferably, the aqueous phase filler comprises hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water in a mass ratio of (15-25): (5-15): (5-15): (20-30).
[0019] Preferably, the bisphenol F epoxy resin is Epikote 862 liquid bisphenol F epoxy resin; the polyamide curing agent is polyamide epoxy curing agent 5140 and / or polyamide epoxy curing agent 2636; and / or the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
[0020] Compared with the prior art, the present invention has at least the following beneficial effects:
[0021] (1) The present invention significantly improves the toughness and hardness of the material by introducing cellulose-modified alumina particles into the epoxy resin. The alumina particles are hard fillers that enhance the load bearing capacity and impact resistance of the material. In addition, the natural polymer structure of cellulose enhances the interfacial adhesion and further improves the overall toughness of the material. The cellulose-modified alumina / epoxy resin material of the present invention fully utilizes the advantages of the natural polymer structure of cellulose. The use of cellulose-modified alumina as a filler can effectively avoid the problem of material fatigue or cracks that are prone to occur in epoxy resin materials under high loads. In addition, the alumina particles have good thermal stability, so that the epoxy resin material can still maintain excellent performance in a high temperature environment. The excellent thermal stability is suitable for high-temperature industrial applications. The use of cellulose from natural sources for chemical modification not only improves the overall mechanical properties of the material, but also reduces the impact on the environment. Compared with epoxy resin materials using traditional chemical synthetic materials, the epoxy resin material is more environmentally friendly and enhances the environmental friendliness of the material. Existing epoxy resin materials are usually reinforced with unmodified inorganic fillers (such as untreated alumina particles) or synthetic fibers. Although these materials provide a certain degree of strength improvement, they are limited in terms of interfacial adhesion, toughness enhancement and environmental friendliness.
[0022] (2) The cellulose-modified alumina / epoxy resin material of the present invention utilizes renewable materials (microcrystalline cellulose) and a relatively environmentally friendly chemical treatment method, thereby reducing the risk of environmental pollution. The cellulose-modified alumina / epoxy resin composite material prepared by the present invention combines the advantages of high-performance modified alumina particles and natural polymer microcrystalline cellulose, and is not only superior to the prior art in terms of mechanical properties and heat resistance, but also better meets the modern industrial needs of sustainable development and environmental protection.
[0023] (3) Before introducing cellulose on the surface of the alumina particles, the present invention first uses 3-(2,3-epoxypropoxy)propyltrimethoxysilane to modify the alumina particles. The present invention finds that the use of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to modify the alumina particles can introduce epoxy groups on the surface of the alumina, and the epoxy groups can undergo a ring-opening reaction in the presence of potassium carbonate. The introduction of epoxy groups increases the chemical activity of the surface of the alumina particles, allowing them to react more effectively with hydroxyl-containing microcrystalline cellulose, thereby effectively improving the composite of the alumina particles and the microcrystalline cellulose, and further effectively improving the interfacial adhesion between the cellulose-modified alumina particles and the epoxy resin, thereby ensuring that the mechanical strength and toughness of the epoxy resin material are improved. DETAILED DESCRIPTION
[0024] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In a first aspect, the present invention provides a method for preparing a cellulose-modified alumina / epoxy resin material, the method comprising the following steps:
[0026] (1) uniformly dispersing aluminum oxide particles with toluene to obtain an aluminum oxide dispersion;
[0027] (2) adding 3-(2,3-epoxypropoxy)propyltrimethoxysilane to the alumina dispersion and stirring the reaction, and then centrifuging, washing and drying to obtain modified alumina particles; in the present invention, by adding 3-(2,3-epoxypropoxy)propyltrimethoxysilane to the alumina dispersion and stirring the reaction, the reaction of 3-(2,3-epoxypropoxy)propyltrimethoxysilane with the hydroxyl groups on the surface of the alumina particles can be promoted, and the reactive trimethoxysilane group in 3-(2,3-epoxypropoxy)propyltrimethoxysilane can react with the hydroxyl groups on the surface of the alumina, thereby introducing epoxy groups on the surface of the alumina, so that it can be combined with cellulose;
[0028] (3) adding modified alumina particles, microcrystalline cellulose, potassium carbonate and ethanol aqueous solution to toluene and stirring the mixture to react, so as to ensure that the microcrystalline cellulose is uniformly attached to the surface of the alumina particles and fully reacts, and then centrifuging, washing and drying to obtain cellulose modified alumina particles; the epoxy groups introduced on the surface of the modified alumina particles in the present invention are more likely to undergo a ring-opening reaction under potassium carbonate conditions, and potassium carbonate is usually used as a weak base in an aqueous environment. In the system of step (3) of the present invention, an ethanol aqueous solution is added, wherein the presence of water components enables potassium carbonate to promote the ring-opening of the epoxy groups, and the epoxy groups after the ring-opening become more active and can form new covalent bonds with the hydroxyl groups in the microcrystalline cellulose to obtain the cellulose modified alumina particles; in the present invention, the ethanol aqueous solution and toluene mainly act as dispersants in the reaction system to disperse the modified alumina and microcrystalline cellulose particles, so that the reaction in step (3) is carried out in a suspended state, so that the components are evenly dispersed and undergo an effective contact reaction;
[0029] (4) Adding cellulose-modified alumina particles to bisphenol A epoxy resin and mixing them evenly to obtain a cellulose-modified alumina / epoxy resin material; in the present invention, for example, stirring and / or ultrasonic treatment can be used to ensure that the cellulose-modified alumina particles can be evenly dispersed in the bisphenol A epoxy resin, which is beneficial to ensure the uniformity and maximized performance of the obtained cellulose-modified alumina / epoxy resin material; in some specific embodiments of the present invention, the cellulose-modified alumina particles are added in the form of a dispersion, for example, tetrahydrofuran can be used to ultrasonically disperse the cellulose-modified alumina particles evenly to obtain a cellulose-modified alumina tetrahydrofuran dispersion, and then the cellulose-modified alumina tetrahydrofuran dispersion is added to the bisphenol A epoxy resin and stirred evenly to obtain a mixture, and then the mixture is vacuum degassed and the tetrahydrofuran is removed by rotary evaporation to obtain a cellulose-modified alumina / epoxy resin material.
[0030] The present invention significantly improves the toughness and hardness of the material by introducing cellulose-modified alumina particles into the epoxy resin. The alumina particles are hard fillers, which enhance the load bearing capacity and impact resistance of the material. In addition, the natural polymer structure of cellulose enhances the interfacial bonding force, further improving the overall toughness of the material. The cellulose-modified alumina / epoxy resin material in the present invention fully utilizes the advantages of the natural polymer structure of cellulose. The use of cellulose-modified alumina as a filler can effectively avoid the problem of material fatigue or cracks that are easy to occur in the epoxy resin material under high load; and the alumina particles have good thermal stability, so that the epoxy resin material can still maintain excellent performance in a high temperature environment, has excellent thermal stability, and is suitable for high-temperature industrial applications. The use of cellulose from natural sources for chemical modification not only improves the overall mechanical properties of the material, but also reduces the impact on the environment. Compared with epoxy resin materials using traditional chemical synthetic materials, it is more environmentally friendly and enhances the environmental friendliness of the material. Existing epoxy resin materials are usually reinforced with unmodified inorganic fillers (such as untreated alumina particles) or synthetic fibers. Although these materials provide a certain degree of strength improvement, they are limited in terms of interfacial bonding, toughness enhancement and environmental friendliness. Before introducing cellulose on the surface of aluminum oxide particles, the present invention first uses 3-(2,3-epoxypropoxy)propyltrimethoxysilane to modify the aluminum oxide particles. The present invention finds that the use of 3-(2,3-epoxypropoxy)propyltrimethoxysilane to modify the aluminum oxide particles can introduce epoxy groups on the surface of the aluminum oxide, and the epoxy groups can undergo a ring-opening reaction in the presence of potassium carbonate. The introduction of epoxy groups increases the chemical activity of the surface of the aluminum oxide particles, allowing them to react more effectively with hydroxyl-containing microcrystalline cellulose, thereby helping to improve the interface interaction between the aluminum oxide particles and the microcrystalline cellulose, thereby effectively improving the composite of the aluminum oxide particles and the microcrystalline cellulose, and further effectively improving the interface adhesion between the cellulose-modified aluminum oxide particles and the epoxy resin, thereby ensuring that the mechanical strength and toughness of the epoxy resin material are improved.
[0031] The present invention finds that the step of pre-modifying the alumina particles with 3-(2,3-epoxypropoxy)propyltrimethoxysilane is very critical, so that the modified alumina particles can react with microcrystalline cellulose in the presence of toluene, potassium carbonate and ethanol aqueous solution. This process not only enhances the bonding force between the alumina particles and the microcrystalline cellulose, but also improves the mechanical properties, thermal stability and dispersion uniformity of the epoxy resin material. The present invention finds that the key to the successful modification of the cellulose-modified alumina / epoxy resin material lies in the interface bonding force and particle dispersibility. The interface bonding force is crucial to the overall performance of the epoxy resin material. By introducing active groups, the chemical bonding between the alumina particles and the microcrystalline cellulose can be enhanced, thereby improving the toughness and mechanical properties of the epoxy resin material. The good dispersibility of the particles is the key to ensuring the uniformity of the performance of the epoxy resin material. Avoiding particle agglomeration can reduce stress concentration points in the epoxy resin material and improve the strength and durability of the epoxy resin material. The present invention finds that if aluminum oxide particles and microcrystalline cellulose are directly stirred and reacted in toluene, potassium carbonate and ethanol aqueous solution, the surface of the unmodified aluminum oxide particles lacks active groups and is difficult to form an effective chemical bond with the hydroxyl groups on the microcrystalline cellulose, which will also lead to poor interface bonding of the epoxy resin material, affecting the overall performance of the material, and the unmodified aluminum oxide particles are also easy to agglomerate in the epoxy resin matrix, resulting in poor dispersibility. The agglomeration of aluminum oxide particles will form stress concentration points, which will also affect the mechanical properties and durability of the epoxy resin material. Similarly, the present invention finds that if 3-(2,3 -Epoxypropyloxy)propyltrimethoxysilane modified alumina particles and microcrystalline cellulose do not allow the 3-(2,3-epoxypropyloxy)propyltrimethoxysilane modified alumina particles and microcrystalline cellulose to fully react, which will also result in insufficient interfacial bonding strength of the epoxy resin material finally obtained, making the epoxy resin material more susceptible to interfacial delamination or crack propagation under stress, affecting the mechanical properties of the material. Also, since the modified alumina particles do not react with microcrystalline cellulose, the modified alumina particles will be unevenly dispersed in the epoxy resin matrix and will easily agglomerate, resulting in a decrease in the strength and toughness of the epoxy resin material.
[0032] According to some preferred embodiments, in step (1), the ratio of the amount of the aluminum oxide particles to the toluene is 1 g: (40-60) mL; and / or in step (2), the ratio of the amount of the aluminum oxide particles contained in the aluminum oxide dispersion to the 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1 g: (1-3) mL.
[0033] According to some preferred embodiments, in step (3), the dosage ratio of the modified alumina particles to the toluene is 1 g: (40-60) mL; the mass ratio of the modified alumina particles to the microcrystalline cellulose is 1: (0.5-1.5) (e.g., 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4 or 1:1.5); in the present invention, preferably, the mass ratio of the modified alumina particles to the microcrystalline cellulose is 1: (0.5-1.5), which is determined through multiple rounds of experiments to ensure sufficient reaction between the microcrystalline cellulose and the modified alumina particles. This mass ratio can not only improve the interfacial bonding force and enhance the overall mechanical properties of the epoxy resin material, but also an appropriate mass ratio can ensure that the obtained cellulose-modified alumina is evenly dispersed in the epoxy resin matrix to avoid particle agglomeration, thereby improving the uniformity and stability of the material; this In addition, introducing a moderate content of microcrystalline cellulose helps to maintain the processing fluidity and molding properties of the epoxy resin material, making the material easy to operate and mold during processing; the present invention finds that if the content of microcrystalline cellulose is too low, it is difficult to form sufficient bonds on the surface of the modified alumina particles, resulting in insufficient interfacial bonding force, and insufficient microcrystalline cellulose content makes it difficult to effectively improve the dispersibility of the modified alumina particles, which easily leads to particle agglomeration and the formation of stress concentration points, affecting the strength and toughness of the epoxy resin material; conversely, if the content of microcrystalline cellulose is too high, it will significantly increase the viscosity of the material, reduce the processing fluidity, and affect the processing and molding properties of the material, and excessive microcrystalline cellulose may cause more weak interfaces to form inside the epoxy resin material, which will reduce the overall strength and toughness of the material; the present invention accurately determines the preferred mass ratio to ensure the best technical effect by comparing the performance indicators under different mass ratios, providing strong support for the manufacture of higher performance cellulose modified alumina / epoxy resin materials.
[0034] According to some preferred embodiments, in step (3), the amount ratio of the modified alumina particles to the ethanol aqueous solution is 1 g: (2-4) mL; the ethanol aqueous solution is formed by mixing ethanol and water in a volume ratio of (7-9): 1. In the present invention, unless otherwise specified, ethanol refers to anhydrous ethanol; and / or the mass amount of potassium carbonate is 1.5-2.5% (e.g., 1.5%, 2% or 2.5%) of the mass amount of the microcrystalline cellulose.
[0035] According to some preferred embodiments, in step (2) and / or step (3), the temperature of the stirring reaction is 80-100°C (e.g., 80°C, 90°C or 100°C), and the time of the stirring reaction is 18-36h (e.g., 18, 20, 22, 24, 26, 28, 30, 32, 34 or 36h); in the present invention, the rotation speed of the stirring reaction can be, for example, 400-800r / min.
[0036] According to some preferred embodiments, the mass amount of the cellulose modified alumina particles is 1-5% (e.g., 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5% or 5%) of the mass amount of the bisphenol A epoxy resin; in the present invention, it is preferred to control the mass amount of the cellulose modified alumina particles to be 1-5% of the mass amount of the bisphenol A epoxy resin. An appropriate amount of cellulose modified alumina particles can significantly improve the tensile strength, flexural strength and impact strength of the epoxy resin material. This optimized ratio is based on a large number of experiments, which can ensure that the cellulose modified alumina particles have the best reinforcement effect and can It can balance the high performance and good processability of epoxy resin materials, and achieve excellent mechanical reinforcement effect and processing convenience; however, if the addition amount of cellulose modified alumina particles is too low, it is difficult to significantly improve the mechanical properties of epoxy resin materials, and it is impossible to form sufficient interface bonding points in the epoxy resin material, affecting the overall performance of the material; conversely, if too many cellulose modified alumina particles are added, the viscosity of the epoxy resin material will be significantly increased, and the processing fluidity of the material will be reduced; in addition, high concentrations of cellulose modified alumina particles are also prone to agglomeration in the epoxy resin matrix. This agglomeration phenomenon will form stress concentration points, thereby affecting the uniformity and mechanical properties of the epoxy resin material.
[0037] According to some preferred embodiments, the cellulose modified alumina particles are added to the bisphenol A epoxy resin in the form of a dispersion, and step (4) is: using tetrahydrofuran to ultrasonically disperse the cellulose modified alumina particles uniformly to obtain a cellulose modified alumina tetrahydrofuran dispersion, and then adding the cellulose modified alumina tetrahydrofuran dispersion to the bisphenol A epoxy resin and stirring uniformly to obtain a mixture, and then vacuum degassing the mixture and removing the tetrahydrofuran by rotary evaporation to obtain a cellulose modified alumina / epoxy resin material, wherein the mass ratio of the cellulose modified alumina particles to the tetrahydrofuran is 1: (10 to 15).
[0038] According to some preferred embodiments, the particle size of the aluminum oxide particles is 20 to 60 nm; the particle size of the microcrystalline cellulose is 3 to 60 μm; and / or the bisphenol A type epoxy resin is E51 liquid epoxy resin.
[0039] According to some specific embodiments, the preparation of the cellulose modified alumina particles is as follows: first, 1g of alumina particles is ultrasonically treated in 50mL of toluene to obtain a uniformly dispersed alumina dispersion. The present invention does not specifically limit the time of ultrasonic treatment, and those skilled in the art can conventionally select, for example, ultrasonic treatment for 5 to 30 minutes; then 2mL of 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added to the alumina dispersion, and stirred at 90°C for 24h, followed by centrifugation, washing twice with ethanol and drying to obtain modified alumina particles; 1g of modified alumina particles, 50mL of toluene, 1g of microcrystalline cellulose, potassium carbonate and 3mL of ethanol are mixed evenly, stirred at 90°C for 24 hours, then centrifuged, washed twice with toluene, and then dried in a vacuum at 80°C for 24 hours to obtain cellulose modified alumina particles; in the present invention, the mass amount of potassium carbonate is 1.5 to 2.5% of the mass amount of microcrystalline cellulose; the centrifugation is centrifuged at 4000 to 8000 rpm for 2 to 5 minutes.
[0040] In a second aspect, the present invention provides a cellulose-modified alumina / epoxy resin material prepared by the preparation method described in the first aspect of the present invention. The present invention uses cellulose-modified alumina particles combined with epoxy resin to obtain a cellulose-modified alumina / epoxy resin material that can significantly improve the mechanical strength, toughness and thermal stability of the material. The material is suitable for industrial applications that require high performance and high temperature resistance, and can exhibit superior mechanical properties and durability in demanding industrial applications; the cellulose-modified alumina / epoxy resin material obtained by the present invention is not only superior to existing materials in terms of mechanical properties and heat resistance, but also more in line with modern industrial needs for sustainable development and environmental protection.
[0041] In the third aspect, the present invention provides the use of a cellulose-modified alumina / epoxy resin material prepared by the preparation method described in the first aspect of the present invention in the preparation of epoxy resin mold materials or epoxy resin molds, wherein the epoxy resin mold material comprises a cellulose-modified alumina / epoxy resin material, a bisphenol F epoxy resin, a polyamide curing agent, an accelerator and an aqueous phase filler.
[0042] According to some preferred embodiments, the mass ratio of the cellulose modified alumina / epoxy resin material, the bisphenol F epoxy resin, the polyamide curing agent, the accelerator and the aqueous phase filler is 10: (2-8): (3-8): (0.5-2): (50-80).
[0043] According to some preferred embodiments, the aqueous phase filler comprises hydrophilic fumed silica, precipitated silica, nano-titanium dioxide and water in a mass ratio of (15-25): (5-15): (5-15): (20-30); the present invention does not specifically limit the particle size of the hydrophilic fumed silica, precipitated silica and nano-titanium dioxide, and those skilled in the art can make conventional selections; in the present invention, the model of the hydrophilic fumed silica is, for example, HDK T30, the model of the precipitated silica is, for example, ZEODENT 103, and the model of the nano-titanium dioxide is, for example, R-FC5.
[0044] According to some preferred embodiments, the bisphenol F epoxy resin is Epikote 862 liquid bisphenol F epoxy resin; the polyamide curing agent is polyamide epoxy curing agent 5140 and / or polyamide epoxy curing agent 2636, preferably, the polyamide curing agent is a mixture of polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 in a mass ratio of 4:(1-3); and / or the accelerator is 2,4,6-tris(dimethylaminomethyl)phenol (accelerator DMP-30).
[0045] According to some preferred embodiments, the preparation of the epoxy resin mold material comprises the following steps:
[0046] (a) mixing hydrophilic fumed silica, precipitated white carbon black and nano titanium dioxide with water to obtain an aqueous phase filler;
[0047] (b) uniformly mixing the cellulose modified alumina / epoxy resin material, bisphenol F epoxy resin, polyamide curing agent and accelerator, and then adding the aqueous phase filler and mixing uniformly to obtain the epoxy resin mold material; in the present invention, step (a) and step (b) are carried out at room temperature of 25°C.
[0048] According to some preferred embodiments, in step (a) and / or step (b), the uniform mixing is performed by stirring at a rotation speed of 400 to 800 r / min.
[0049] According to some specific embodiments, the preparation of the epoxy resin mold material includes:
[0050] (a) Preparation of aqueous phase filler: hydrophilic fumed silica, precipitated white carbon black and nano titanium dioxide are gradually added to water, and stirred at a speed of 600 r / min until all inorganic particles are evenly dispersed to form a uniform suspension, thereby obtaining an aqueous phase filler;
[0051] (b) The cellulose modified alumina / epoxy resin material, bisphenol F epoxy resin, polyamide curing agent and accelerator are stirred and mixed at a rotation speed of 600 r / min to obtain a resin phase, and then a water phase filler is added to the resin phase at a rotation speed of 600 r / min and the stirring and mixing are continued to obtain an epoxy resin mold material.
[0052] When the epoxy resin mold material is used to prepare a resin mold in the present invention, the epoxy resin mold material can be placed in a molding mold designed in advance according to the resin mold structure (the inner surface of the molding mold is pre-evenly coated with a layer of release agent), and then cured at 30-40°C for 10-18h, and then demolded to obtain the epoxy resin mold.
[0053] The present invention will be further described below by way of examples, but the protection scope of the present invention is not limited to these embodiments.
[0054] Example 1
[0055] ① First, alumina particles (average particle size of 40 nm) were ultrasonically treated in toluene for 15 min to obtain a uniformly dispersed alumina dispersion, and the ratio of alumina particles to toluene was 1 g:50 mL; then 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added to the alumina dispersion, and the mixture was stirred at 90°C and 600 r / min for 24 h, followed by centrifugation (centrifugation at 6000 rpm for 3 min), washing twice with ethanol, and vacuum drying at 80°C for 24 h to obtain modified alumina particles, wherein the alumina dispersion contained alumina particles and 3-(2,3-epoxypropoxy)propyltrimethoxysilane in a ratio of 1:1. g:2mL; then add modified alumina particles, microcrystalline cellulose (average particle size of 30 μm), potassium carbonate and ethanol aqueous solution (ethanol aqueous solution is a mixture of ethanol and water in a volume ratio of 8:2) to toluene, and stir the reaction at 90°C and 600r / min for 24 hours, then centrifuge (centrifuge at 6000 rpm for 3 minutes), wash twice with toluene, and then vacuum dry at 80°C for 24 hours to obtain cellulose modified alumina particles, wherein the amount ratio of modified alumina particles, toluene, microcrystalline cellulose and ethanol aqueous solution is 1g:50mL:1g:3mL, and the mass amount of potassium carbonate is 2% of the mass amount of microcrystalline cellulose.
[0056] ② The cellulose modified alumina particles obtained in step ① are ultrasonically treated with tetrahydrofuran for 15 minutes to be evenly dispersed to obtain a cellulose modified alumina tetrahydrofuran dispersion, and then the cellulose modified alumina tetrahydrofuran dispersion is added to a bisphenol A epoxy resin (E51 liquid epoxy resin) and stirred at a speed of 600 r / min for 20 minutes to obtain a mixture, and then the mixture is vacuum degassed and the tetrahydrofuran is removed by rotary evaporation to obtain a cellulose modified alumina / epoxy resin material; the mass ratio of the cellulose modified alumina particles to the tetrahydrofuran is 1:13; the mass of the cellulose modified alumina particles contained in the cellulose modified alumina tetrahydrofuran dispersion is 1% of the mass of the bisphenol A epoxy resin.
[0057] ③ Using water to stir and mix the hydrophilic fumed silica, precipitated silica and nano titanium dioxide at a speed of 600 r / min to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water is 20:10:10:25; the cellulose modified alumina / epoxy resin material and bisphenol F epoxy resin (Epikote 862 liquid bisphenol F type epoxy resin), polyamide curing agent and accelerator DMP-30 are stirred and mixed uniformly at a speed of 600r / min in a mass ratio of 10:5:7:1 to obtain a resin phase, and an aqueous phase filler is added to the resin phase at a speed of 600r / min and continued to be stirred and mixed uniformly at a speed of 600r / min to obtain an epoxy resin mold material; wherein the polyamide curing agent is a mixture of polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 in a mass ratio of 4:3; the mass ratio of cellulose modified alumina / epoxy resin material, bisphenol F type epoxy resin, polyamide curing agent, accelerator DMP-30 and aqueous phase filler is 10:5:7:1:65.
[0058] Example 2
[0059] Embodiment 2 is substantially the same as Embodiment 1, except that:
[0060] ② The cellulose modified alumina particles obtained in step ① are uniformly dispersed by ultrasonication for 15 minutes using tetrahydrofuran to obtain a cellulose modified alumina tetrahydrofuran dispersion, and then the cellulose modified alumina tetrahydrofuran dispersion is added to bisphenol A epoxy resin (E51 liquid epoxy resin) and stirred at a speed of 600 r / min for 20 minutes to obtain a mixture, and then the mixture is vacuum degassed and the tetrahydrofuran is removed by rotary evaporation to obtain a cellulose modified alumina / epoxy resin material; the mass ratio of the cellulose modified alumina particles to tetrahydrofuran is 1:13; the mass of the cellulose modified alumina particles contained in the cellulose modified alumina tetrahydrofuran dispersion is 3% of the mass of the bisphenol A epoxy resin.
[0061] Example 3
[0062] Embodiment 3 is substantially the same as Embodiment 1, except that:
[0063] ② The cellulose-modified alumina particles obtained in step ① are uniformly dispersed by ultrasonication for 15 minutes using tetrahydrofuran to obtain a cellulose-modified alumina-tetrahydrofuran dispersion; the cellulose-modified alumina-tetrahydrofuran dispersion is then added to a bisphenol A epoxy resin (E51 liquid epoxy resin) and stirred at a speed of 600 r / min for 20 minutes to obtain a mixture; the mixture is then vacuum-degassed and the tetrahydrofuran is removed by rotary evaporation to obtain a cellulose-modified alumina / epoxy resin material; the mass ratio of the cellulose-modified alumina to the tetrahydrofuran is 1:13; the mass of the cellulose-modified alumina particles contained in the cellulose-modified alumina-tetrahydrofuran dispersion is 5% of the mass of the bisphenol A epoxy resin.
[0064] Example 4
[0065] Embodiment 4 is substantially the same as Embodiment 1, except that:
[0066] ① First, alumina particles (average particle size of 40 nm) were ultrasonically treated in toluene for 15 min to obtain a uniformly dispersed alumina dispersion, and the ratio of alumina particles to toluene was 1 g:50 mL; then 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added to the alumina dispersion, and the reaction was stirred at 90°C and 600 r / min for 24 h, followed by centrifugation (centrifugation at 6000 rpm for 3 minutes), washing twice with ethanol, and vacuum drying at 80°C for 24 h to obtain modified alumina particles, wherein the alumina dispersion contained alumina particles and 3-(2,3-epoxypropoxy)propyltrimethoxysilane in a ratio of 1 g:50 mL. :2mL; then add modified alumina particles, microcrystalline cellulose (average particle size of 30μm), potassium carbonate and ethanol aqueous solution (ethanol aqueous solution is a mixture of ethanol and water in a volume ratio of 8:2) to toluene, and stir the reaction at 90°C and 600r / min for 24 hours, then centrifuge (centrifuge at 6000 rpm for 3 minutes), wash twice with toluene, and then vacuum dry at 80°C for 24 hours to obtain cellulose modified alumina particles, wherein the amount ratio of modified alumina particles, toluene, microcrystalline cellulose and ethanol aqueous solution is 1g:50mL:0.3g:3mL, and the mass amount of potassium carbonate is 2% of the mass amount of microcrystalline cellulose.
[0067] Example 5
[0068] Example 5 is substantially the same as Example 1, except that:
[0069] ① First, alumina particles (average particle size of 30 nm) were ultrasonically treated in toluene for 15 min to obtain a uniformly dispersed alumina dispersion, and the ratio of alumina particles to toluene was 1 g:50 mL; then 3-(2,3-epoxypropoxy)propyltrimethoxysilane was added to the alumina dispersion, and the mixture was stirred at 90°C and 600 r / min for 24 h, followed by centrifugation (centrifugation at 6000 rpm for 3 min), washing twice with ethanol, and vacuum drying at 80°C for 24 h to obtain modified alumina particles, wherein the alumina dispersion contained alumina particles and 3-(2,3-epoxypropoxy)propyltrimethoxysilane in a ratio of 1:1. g:2mL; then add modified alumina particles, microcrystalline cellulose (average particle size of 30 μm), potassium carbonate and ethanol aqueous solution (ethanol aqueous solution is a mixture of ethanol and water in a volume ratio of 8:2) to toluene, and stir the reaction at 90°C and 600 r / min for 24 hours, then centrifuge (centrifuge at 6000 rpm for 3 minutes), wash twice with toluene, and then vacuum dry at 80°C for 24 hours to obtain cellulose modified alumina particles, wherein the amount ratio of modified alumina particles, toluene, microcrystalline cellulose and ethanol aqueous solution is 1g:50mL:2g:3mL, and the mass amount of potassium carbonate is 2% of the mass amount of microcrystalline cellulose.
[0070] Example 6
[0071] Embodiment 6 is substantially the same as Embodiment 1, except that:
[0072] ② The cellulose modified alumina particles obtained in step ① are ultrasonically treated with tetrahydrofuran for 15 minutes to be evenly dispersed to obtain a cellulose modified alumina tetrahydrofuran dispersion, and then the cellulose modified alumina tetrahydrofuran dispersion is added to bisphenol A epoxy resin (E51 liquid epoxy resin) and stirred at a speed of 600 r / min for 20 minutes to obtain a mixture, and then the mixture is vacuum degassed and the tetrahydrofuran is removed by rotary evaporation to obtain a cellulose modified alumina / epoxy resin material; the mass ratio of the cellulose modified alumina particles to tetrahydrofuran is 1:13; the mass of the cellulose modified alumina particles contained in the cellulose modified alumina tetrahydrofuran dispersion is 0.3% of the mass of the bisphenol A epoxy resin.
[0073] Example 7
[0074] Example 7 is substantially the same as Example 1, except that:
[0075] ② The cellulose modified alumina particles obtained in step ① are ultrasonically treated with tetrahydrofuran for 15 minutes to be evenly dispersed to obtain a cellulose modified alumina tetrahydrofuran dispersion, and then the cellulose modified alumina tetrahydrofuran dispersion is added to a bisphenol A epoxy resin (E51 liquid epoxy resin) and stirred at a speed of 600 r / min for 20 minutes to obtain a mixture, and then the mixture is vacuum degassed and the tetrahydrofuran is removed by rotary evaporation to obtain a cellulose modified alumina / epoxy resin material; the mass ratio of the cellulose modified alumina particles to the tetrahydrofuran is 1:13; the mass of the cellulose modified alumina particles contained in the cellulose modified alumina tetrahydrofuran dispersion is 8% of the mass of the bisphenol A epoxy resin.
[0076] Comparative Example 1
[0077] The hydrophilic fumed silica, precipitated silica and nano titanium dioxide were stirred and mixed uniformly at a speed of 600 r / min with water to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water was 20:10:10:25; bisphenol A epoxy resin (E51 liquid epoxy resin), bisphenol F epoxy resin (Epikote862 liquid bisphenol F epoxy resin), polyamide curing agent and accelerator DMP-30 were stirred and mixed uniformly at a speed of 600 r / min to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water was 20:10:10:25; bisphenol A epoxy resin (E51 liquid epoxy resin), bisphenol F epoxy resin (Epikote862 liquid bisphenol F epoxy resin), polyamide curing agent and accelerator DMP-30 were stirred and mixed uniformly at a speed of 600 r / min to obtain an aqueous filler. The mixture was stirred and mixed evenly at a speed of 0 r / min to obtain a resin phase, and a water phase filler was added to the resin phase at a speed of 600 r / min and continued to be stirred and mixed evenly at a speed of 600 r / min to obtain an epoxy resin mold material; wherein the polyamide curing agent was prepared by mixing polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 in a mass ratio of 4:3; the mass ratio of bisphenol A epoxy resin, bisphenol F epoxy resin, polyamide curing agent, accelerator DMP-30 and water phase filler was 10:5:7:1:65.
[0078] Comparative Example 2
[0079] ① Add alumina particles (average particle size of 40 nm), microcrystalline cellulose (average particle size of 30 μm), potassium carbonate and ethanol aqueous solution (ethanol aqueous solution is a mixture of ethanol and water in a volume ratio of 8:2) to toluene, and stir the reaction at 90°C and 600 r / min for 24 hours, then centrifuge (centrifuge at 6000 rpm for 3 minutes), wash twice with toluene, and then vacuum dry at 80°C for 24 hours to obtain cellulose-modified alumina particles, wherein the amount ratio of alumina particles, toluene, microcrystalline cellulose and ethanol aqueous solution is 1 g:50 mL:1 g:3 mL, and the mass amount of potassium carbonate is 2% of the mass amount of microcrystalline cellulose.
[0080] ② The cellulose modified alumina particles obtained in step ① are ultrasonically treated with tetrahydrofuran for 15 minutes to be evenly dispersed to obtain a cellulose modified alumina tetrahydrofuran dispersion, and then the cellulose modified alumina tetrahydrofuran dispersion is added to a bisphenol A epoxy resin (E51 liquid epoxy resin) and stirred at a speed of 600 r / min for 20 minutes to obtain a mixture, and then the mixture is vacuum degassed and the tetrahydrofuran is removed by rotary evaporation to obtain a cellulose modified alumina / epoxy resin material; the mass ratio of the cellulose modified alumina particles to the tetrahydrofuran is 1:13; the mass of the cellulose modified alumina particles contained in the cellulose modified alumina tetrahydrofuran dispersion is 1% of the mass of the bisphenol A epoxy resin.
[0081] ③ Using water to stir and mix the hydrophilic fumed silica, precipitated silica and nano titanium dioxide at a speed of 600 r / min to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water is 20:10:10:25; the cellulose modified alumina / epoxy resin material and bisphenol F epoxy resin (Epikote 862 liquid bisphenol F type epoxy resin), polyamide curing agent and accelerator DMP-30 are stirred and mixed uniformly at a speed of 600r / min in a mass ratio of 10:5:7:1 to obtain a resin phase, and an aqueous phase filler is added to the resin phase at a speed of 600r / min and continued to be stirred and mixed uniformly at a speed of 600r / min to obtain an epoxy resin mold material; wherein the polyamide curing agent is a mixture of polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 in a mass ratio of 4:3; the mass ratio of cellulose modified alumina / epoxy resin material, bisphenol F type epoxy resin, polyamide curing agent, accelerator DMP-30 and aqueous phase filler is 10:5:7:1:65.
[0082] Comparative Example 3
[0083] ① First, alumina particles (average particle size of 40 nm) are ultrasonically treated in toluene for 15 minutes to obtain a uniformly dispersed alumina dispersion, and the ratio of alumina particles to toluene is 1 g:50 mL; then 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added to the alumina dispersion, and the reaction is stirred at 90°C and 600 r / min for 24 hours, followed by centrifugation (centrifugation at 6000 rpm for 3 minutes), washing twice with ethanol and vacuum drying at 80°C for 24 hours to obtain modified alumina particles; the alumina dispersion contains alumina particles and 3-(2,3-epoxypropoxy)propyltrimethoxysilane in a ratio of 1 g:2 mL.
[0084] ② The modified alumina particles and microcrystalline cellulose (average particle size of 30 μm) obtained in step ① are ultrasonically treated with tetrahydrofuran for 15 minutes to be uniformly dispersed to obtain a tetrahydrofuran dispersion, and then the tetrahydrofuran dispersion is added to bisphenol A epoxy resin (E51 liquid epoxy resin) and stirred at a speed of 600 r / min for 20 minutes to obtain a mixture, and then the mixture is vacuum degassed and the tetrahydrofuran is removed by rotary evaporation to obtain a modified epoxy resin material; the mass ratio of the modified alumina particles and the microcrystalline cellulose to the mass of the tetrahydrofuran is 1:13; the mass ratio of the modified alumina particles to the microcrystalline cellulose is 1:1, and the mass sum of the modified alumina particles and the microcrystalline cellulose contained in the tetrahydrofuran dispersion is 1% of the mass of the bisphenol A epoxy resin.
[0085] ③ Using water to stir and mix the hydrophilic fumed silica, precipitated silica and nano titanium dioxide at a speed of 600 r / min to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water is 20:10:10:25; the modified epoxy resin material obtained in step ② and the bisphenol F epoxy resin (Epikote 862 liquid bisphenol F type epoxy resin), polyamide curing agent and accelerator DMP-30 are stirred and mixed uniformly at a speed of 600r / min at a mass ratio of 10:5:7:1 to obtain a resin phase, and an aqueous phase filler is added to the resin phase at a speed of 600r / min and continued to be stirred and mixed uniformly at a speed of 600r / min to obtain an epoxy resin mold material; wherein the polyamide curing agent is prepared by mixing polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 at a mass ratio of 4:3; the mass ratio of modified epoxy resin material, bisphenol F type epoxy resin, polyamide curing agent, accelerator DMP-30 and aqueous phase filler is 10:5:7:1:65.
[0086] Comparative Example 4
[0087] ① Dissolve microcrystalline cellulose (average particle size of 30 μm) in an ionic liquid, place it in a water bath at 85°C and stir until the microcrystalline cellulose is dissolved to obtain a cellulose solution, add butyric anhydride to the cellulose solution and react at 80°C for 1 hour, add acetic anhydride and continue to react at 85°C for 2 hours, and stir continuously during the entire reaction process. The extracted product is precipitated with methanol, washed 3 times, and dried in a vacuum drying oven at 80°C for 20 hours to obtain cellulose acetate butyrate, wherein the mass ratio of microcrystalline cellulose to ionic liquid is 1:20, and the molar ratio of microcrystalline cellulose, butyric anhydride and acetic anhydride is 1:4:4.
[0088] ② Ultrasonic treatment of alumina particles (average particle size of 40 nm) in toluene for 15 minutes to obtain a uniformly dispersed alumina dispersion, the amount ratio of alumina particles to toluene is 1 g:50 mL; then 3-(2,3-epoxypropoxy)propyltrimethoxysilane is added to the alumina dispersion, and the reaction is stirred at 90°C and 600 r / min for 24 hours, followed by centrifugation (centrifugation at 6000 rpm for 3 minutes), washing twice with ethanol and vacuum drying at 80°C for 24 hours to obtain modified alumina particles, the alumina dispersion contains alumina particles and 3-(2,3-epoxypropoxy)propyltrimethoxysilane in a ratio of 1 g:2 mL.
[0089] ③ Using tetrahydrofuran to ultrasonically treat the cellulose acetate butyrate obtained in step ① and the modified alumina particles obtained in step ② for 15 minutes to disperse them uniformly, to obtain a tetrahydrofuran dispersion, and then add the tetrahydrofuran dispersion to bisphenol A epoxy resin (E51 liquid epoxy resin) and stir at a speed of 600 r / min for 20 minutes to obtain a mixture, and then vacuum degas the mixture and remove the tetrahydrofuran by rotary evaporation to obtain a modified epoxy resin material; wherein the mass ratio of the sum of the mass of the cellulose acetate butyrate and the modified alumina particles to the mass of the tetrahydrofuran is 1:13; the mass ratio of the cellulose acetate butyrate and the modified alumina particles is 1:1, and the sum of the mass of the cellulose acetate butyrate and the modified alumina particles contained in the tetrahydrofuran dispersion is 1% of the mass of the bisphenol A epoxy resin.
[0090] ④ Using water to stir and mix the hydrophilic fumed silica, precipitated silica and nano titanium dioxide at a speed of 600r / min to obtain an aqueous filler, wherein the mass ratio of the hydrophilic fumed silica, precipitated silica, nano titanium dioxide and water is 20:10:10:25; the modified epoxy resin material obtained in step ③ and the bisphenol F epoxy resin (Epikote 862 liquid bisphenol F type epoxy resin), polyamide curing agent and accelerator DMP-30 are stirred and mixed uniformly at a speed of 600r / min at a mass ratio of 10:5:7:1 to obtain a resin phase, and an aqueous phase filler is added to the resin phase at a speed of 600r / min and continued to be stirred and mixed uniformly at a speed of 600r / min to obtain an epoxy resin mold material; wherein the polyamide curing agent is prepared by mixing polyamide epoxy curing agent 5140 and polyamide epoxy curing agent 2636 at a mass ratio of 4:3; the mass ratio of modified epoxy resin material, bisphenol F type epoxy resin, polyamide curing agent, accelerator DMP-30 and aqueous phase filler is 10:5:7:1:65.
[0091] In order to evaluate the performance of the epoxy resin mold material, the epoxy resin mold material prepared in each embodiment and each comparative example was cured at 35° C. for 12 hours to obtain a cured sample of the epoxy resin mold material, and then the bending strength and hardness were tested. The results are shown in Table 1.
[0092] Table 1
[0093]
[0094]
[0095] It can be seen from the data in Table 1 that the bending strength of the epoxy resin mold material prepared in some preferred embodiments of the present invention is as high as 13 MPa or more, indicating that it has good structural integrity and bending resistance when subjected to external pressure, indicating that the epoxy resin mold material has high toughness, and the greater the bending strength of the prepared epoxy resin mold material, the greater its toughness; in some preferred embodiments, the hardness of the obtained epoxy resin mold material is as high as 68D or more, indicating that the material has high hardness and wear resistance, and is suitable for manufacturing ceramic molds that need to withstand large mechanical loads.
[0096] Parts of the present invention that are not described in detail are well known to those skilled in the art.
[0097] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a cellulose-modified alumina / epoxy resin material, characterized in that: The method comprises the following steps: (1) Dispersing aluminum oxide particles uniformly with toluene to obtain an aluminum oxide dispersion; (2) adding 3-(2,3-epoxypropoxy)propyltrimethoxysilane to the alumina dispersion and stirring the mixture for reaction, and then centrifuging, washing and drying the mixture to obtain modified alumina particles; (3) adding modified alumina particles, microcrystalline cellulose, potassium carbonate and ethanol aqueous solution into toluene and stirring to react, and then centrifuging, washing and drying to obtain cellulose modified alumina particles; (4) Adding cellulose-modified alumina particles to bisphenol A epoxy resin and mixing them evenly to obtain a cellulose-modified alumina / epoxy resin material; the mass amount of the cellulose-modified alumina particles is 1 to 5% of the mass amount of the bisphenol A epoxy resin; the cellulose-modified alumina particles are added to the bisphenol A epoxy resin in the form of a dispersion.
2. The preparation method according to claim 1, characterized in that: In step (1), the ratio of the aluminum oxide particles to the toluene is 1 g: (40-60) mL; In step (2), the ratio of the aluminum oxide particles contained in the aluminum oxide dispersion to the 3-(2,3-epoxypropoxy)propyltrimethoxysilane is 1 g: (1-3) mL; In step (3), the ratio of the modified alumina particles to the toluene is 1 g: (40-60) mL, the mass ratio of the modified alumina particles to the microcrystalline cellulose is 1: (0.5-1.5), and the ratio of the modified alumina particles to the ethanol aqueous solution is 1 g: (2-4) mL; In step (3), the ethanol aqueous solution is prepared by mixing ethanol and water in a volume ratio of (7-9):1; and / or In step (3), the mass amount of potassium carbonate is 1.5-2.5% of the mass amount of microcrystalline cellulose.
3. The preparation method according to claim 1, characterized in that: In step (2) and / or step (3), the stirring reaction temperature is 80-100° C., and the stirring reaction time is 18-36 hours.
4. The preparation method according to claim 1, characterized in that: Step (4) comprises: uniformly dispersing cellulose-modified alumina particles by ultrasonication using tetrahydrofuran to obtain a cellulose-modified alumina tetrahydrofuran dispersion; then adding the cellulose-modified alumina tetrahydrofuran dispersion to a bisphenol A epoxy resin and stirring the mixture to obtain a mixture; then vacuum degassing the mixture and removing the tetrahydrofuran by rotary evaporation to obtain a cellulose-modified alumina / epoxy resin material; wherein the mass ratio of the cellulose-modified alumina particles to the tetrahydrofuran is 1:(10-15).
5. The preparation method according to claim 1, characterized in that: The particle size of the aluminum oxide particles is 20-60 nm; The particle size of the microcrystalline cellulose is 3-60 μm; and / or The bisphenol A type epoxy resin is E51 liquid epoxy resin.
6. A cellulose-modified alumina / epoxy resin material prepared by the preparation method according to any one of claims 1 to 5.
7. Use of the cellulose-modified alumina / epoxy resin material prepared by the preparation method according to any one of claims 1 to 5 in the preparation of epoxy resin mold materials or epoxy resin molds, characterized in that: The epoxy resin mold material comprises cellulose-modified alumina / epoxy resin material, bisphenol F epoxy resin, polyamide curing agent, accelerator and water-phase filler.
8. The use according to claim 7, characterized in that: The mass ratio of the cellulose modified alumina / epoxy resin material, the bisphenol F epoxy resin, the polyamide curing agent, the accelerator and the aqueous phase filler is 10: (2-8): (3-8): (0.5-2): (50-80).
9. The use according to claim 7, characterized in that: The aqueous phase filler comprises hydrophilic fumed silica, precipitated white carbon black, nano titanium dioxide and water in a mass ratio of (15-25): (5-15): (5-15): (20-30).
10. The use according to claim 7, characterized in that: The bisphenol F epoxy resin is Epikote 862 liquid bisphenol F epoxy resin; The polyamide curing agent is polyamide epoxy curing agent 5140 and / or polyamide epoxy curing agent 2636; and / or The accelerator is 2,4,6-tris(dimethylaminomethyl)phenol.
Citation Information
Patent Citations
Preparation method of nano-SiO2 / cellulose composite separating membranes
CN103170255A
Modified alumina composite material, copper-coated substrate and preparation method of copper-coated substrate
CN104371274A